Racial disparities in nephrectomy and mortality among patients with renal cell carcinoma: Findings from SEER - Joshua Ikuemonisan; Taiwo Opeyemi Aremu; Isaac Oyejinmi; Christopher Ajala; Nnabuchi Anikpezie; Oyindamola Akinso; Mutsa Mtengwa; Adeyemo David; Olugbenga Olokede; Oluwakayode Adejoro (Public Library of Science (PLoS), 2023)
Purpose To assess racial differences in the receipt of nephrectomy in patients diagnosed RCC in the US. Materials and methods 2005 to 2015 data from the SEER database was analyzed and 70,059 patients with RCC were identified. We compared demographic and tumor characteristics between black patients and white patients. We applied logistic regression to assess the association between race and the odds of the receipt of nephrectomy. We also applied Cox proportional hazards model to assess the impact of race on cancer-specific mortality (CSM) and all-cause mortality (ACM) in patients diagnosed with RCC in the US. Results Black patients had 18% lower odds of receiving nephrectomy compared to white patients (p < 0.0001). The odds of the receipt of nephrectomy also reduced with age at diagnosis. In addition, patients with T3 stage had the greatest odds of receiving nephrectomy when compared to T1 (p < 0.0001). There was no difference in the risk of cancer-specific mortality between black patients and white patients; black patients had 27% greater odds of all-cause mortality than white patients (p < 0.0001). Patients who did not receive nephrectomy had a 42% and 35% higher risk of CSM and ACM respectively, when compared to patients who received nephrectomy. Conclusions Black patients diagnosed with RCC in the US have a greater ACM risk and are less likely than white patients to receive nephrectomy. Systemic changes are needed to eliminate racial disparity in the treatment and outcomes of RCC in the US.